Making sense of entrepreneurial intent: a look at gender and entrepreneurial personal theory. Issue 5 (26th June 2020) - Matherne III, Curtis F.; Bendickson, Joshua S.; Santos, Susana C.; Taylor, Erik C.
Abstract : Purpose: Individuals adopt differing perceptions of entrepreneurial types, including small businesses, scalable businesses and social businesses. This study aims to suggest that individuals' entrepreneurial personal theory (EPT: learning from experiences that informs how an individual conceptualizes entrepreneurship) influences entrepreneurial intent, and that sensemaking facilitates this process such that those with a clearer understanding of different entrepreneurship paths are more likely to pursue opportunities. Design/methodology/approach: This study theorizes and empirically tests whether EPT affects an individual's intent to start a small business, a scalable business or a social enterprise and how gender moderates the relationship between EPT and entrepreneurial intent. Primary survey data were collected from undergraduate business students and working adults. Findings: The results indicate that EPTs characterized by small business, scalable business and social entrepreneurship have a positive association with entrepreneurial intentions. However, gender interaction effects showed that for women, an EPT characterized as small business has a weaker relationship with entrepreneurial intent, whereas an EPT characterized as social entrepreneurship has a stronger relationship with entrepreneurial intent. The notions that gender directly affects personal conceptions of entrepreneurship and that women may have not been exposed to all facets of entrepreneurship are addressed. Research limitations/implications: Other variables not included in this study could also influence the relationship between how the type of entrepreneurship may shape entrepreneurial intent and how such relationship may be influenced by gender. Implications for entrepreneurship education and curriculum development are presented. Originality/value: Integrating the EPT and sensemaking to uncover gender differences in the development of entrepreneurial intentions is a novel theoretical discussion.